2013
DOI: 10.1089/thy.2011.0480
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Innate Immune Responses in the Thyroid Gland: Potential to Sense Danger and a Possible Trigger for Autoimmune Reactions

Abstract: Background: Autoimmune thyroid disease is an archetypal organ-specific autoimmune disorder that is characterized by the production of thyroid autoantibodies and lymphocytic infiltration into the thyroid. However, the underlying mechanisms by which specific thyroid antibodies are produced are largely unknown. Recent studies have shown that innate immune responses affect both the phenotype and the severity of autoimmune reactions. Moreover, it appears that even non-immune cells, including thyroid cells, have an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 54 publications
1
41
1
1
Order By: Relevance
“…Highest overexpression (5.77-fold) was observed with the Tpo (thyroid peroxidase) gene. This contrasts with findings from previous studies reporting either no effect of iodide treatment on Tpo expression (23,39,40) or even downregulation of its expression (41,42) in thyroid cells or lines. The reasons for this discrepancy are unclear but may be due to the different protocols used.…”
Section: Kolypetri and Carayanniotiscontrasting
confidence: 99%
“…Highest overexpression (5.77-fold) was observed with the Tpo (thyroid peroxidase) gene. This contrasts with findings from previous studies reporting either no effect of iodide treatment on Tpo expression (23,39,40) or even downregulation of its expression (41,42) in thyroid cells or lines. The reasons for this discrepancy are unclear but may be due to the different protocols used.…”
Section: Kolypetri and Carayanniotiscontrasting
confidence: 99%
“…In addition, poly (I:C) administration aggravates inflammation of excessive iodine-induced thyroiditis in NOD mice, and evidence of the severity of thyroid follicle destruction and amount of lymphocyte infiltration has been reported (25). DNA microarray analysis has shown that stimulation of cultured human thyroid follicles with dsRNA [poly (I:C)] can cause activation of inflammatory responses and upregulation of a variety of related genes, including pro-inflammatory cytokines (IL-6) and chemokines (27). The results of the present study are consistent with previous studies suggesting that TLR3 may be involved in the development of AITD.…”
Section: Discussionmentioning
confidence: 99%
“…Although a relation between CiPxt and peroxidase activity could be hypothesized, the present data on CiPxt expression by these zones do not allow to establish a relationship between CiPxt gene expression and thyroid-like activity during the inflammatory response. However, it is known that, in humans, proinflammatory cytokines cause thyroid inflammatory disorders (Ajjan et al, 1996) and a recent paper reports on thyroid cells that express functional sensors for exogenous and endogenous dangers, and they are capable of launching innate immune responses without the assistance of immune cells (Kawashima et al, 2012).…”
Section: Discussionmentioning
confidence: 99%